Computer vision applications : third Workshop, WCVA 2018, held in conjunction with ICVGIP 2018, Hyderabad, India, December 18, 2018, Revised selected papers /: third Workshop, WCVA 2018, held in conjunction with ICVGIP 2018, Hyderabad, India, December 18, 2018, Revised selected papers. (2019) - Unknown
No abstract available